The Ukrainian children emergency: How the Pediatric Oncology Unit of Turin supports cancer patients and their families who have escaped war. Issue 9 (20th May 2022) - Zucchetti, Giulia; Battaglini, Chiara; Ciappina, Sabrina; Geuna, Tiziana; Giordano, Mario; Peirolo, Claudia; Roccia, Elvia; Asaftei, Sebastian; Quarello, Paola; Fagioli, Franca
Abstract: Due to the war in Ukraine, many children have been killed and those who suffer from severe diseases, such as oncological pathologies, are facing serious challenges as their treatment is interrupted. The objective of this report is to describe one of the first Italian humanitarian expeditions launched to rescue children and their families to provide them with the best possible cancer care. The Pediatric Oncology Unit of Turin has welcomed 60 Ukrainians who are patients, caregivers and siblings. This report underlines the activities that have been implemented to offer this new type of patient the best possible care.